The effect of impediments to responding to defective goods - a comparative jurisprudential study - - Saleh Kaddouri Sabah (Islamic Sciences Journal, 2024)
ABSTRACT This issue is of great importance to society, in order to take into account what is permissible and beware of what is forbidden, especially since people have increased their dealings with buying and selling contracts. Therefore, I have discussed what is permissible and what is not permissible in returning a commodity that has been subjected to fraud by the seller, as I explained that the buyer has the option to To hold the seller back from the price equal to the defect, or return it to the seller and give him the price of the defect that occurred to him, and the removal of the defect from the sold item is an impediment to returning the sold item to the seller; Unless it is possible that the defect will return to the commodity again, and if the defect is removed by itself or by the seller removing it, then he is prevented from responding to the seller. If the buyer learns of the defect after selling the commodity, he has a right to return to the one who sold it to repair the defect. If two people bought a commodity and found a defect in it, and one of them wanted it. If the item is returned to the person who sold it and the other refuses to return it, then one of them has the right to return the item to the seller even if the second refuses to return it.